Composite glass fiber board and preparation method thereof

By constructing a composite fiberglass board with dynamic imine bond crosslinking, the problem of degradation of performance and insufficient damage repair ability in long-term use of fiberglass board is solved, and excellent mechanical properties and efficient self-repairing ability are achieved.

CN119592050APending Publication Date: 2025-03-11JIANGSU KEWO HOME FURNISHING TECH CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411930212.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

Existing fiberglass boards are susceptible to factors such as mechanical damage, microcrack proliferation and environmental erosion during long-term use, resulting in a decline in material performance and weak damage repair ability, making it difficult to recover itself.

Method used

By constructing a dual-network structure with dynamic imine bond crosslinking, using polyurethane and glass fiber as the main chain structure, m-phenylenediamine and benzaldehyde form a dynamic imine bond network through condensation reaction, and combining ultrasonic thermal pressing to form a composite glass fiberboard with a dual-network reinforced structure.

Benefits of technology

It significantly improves the mechanical properties, self-repair ability and durability of fiberglass boards, and can achieve rapid repair through environmental stimulation after damage, and the repair process can be repeated multiple times without complicated operations.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005210097250000071
    Figure BDA0005210097250000071
  • Figure BDA0005210097250000081
    Figure BDA0005210097250000081
Patent Text Reader

Abstract

The invention relates to the field of preparation of glass fiber boards, in particular to a composite glass fiber board and a preparation method thereof. According to the composite glass fiber board provided by the invention, a dynamic imine bond cross-linked dual-network structure is constructed, so that the mechanical property and durability of the glass fiber board are remarkably improved, and the composite glass fiber board has high-efficiency repeated self-repairing capability, is wide in application field, can be applied to the building fields such as home furnishing boards and the like, and also can be applied to the building fields such as building materials. The method is also suitable for automobile manufacturing, aerospace and other fields. The invention further provides a preparation method of the composite glass fiber board, the preparation method is simple and easy to implement, and expensive equipment is not needed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of glass fiber board preparation, and in particular to a composite glass fiber board and a preparation method thereof. Background Art

[0002] Glass fiber board, with its many advantages such as high strength, excellent corrosion resistance and lightweight, has shown wide application potential in many fields such as construction and home furnishing panels. This material can not only greatly improve the stability and safety of building structures, but also reduce the overall weight and improve construction efficiency while meeting design requirements. However, in the long-term use process, glass fiber board is not impeccable. It is susceptible to the combined effects of multiple factors such as mechanical damage, microcrack expansion and environmental erosion, which leads to a gradual decline in material performance, and even complete failure in severe cases. Mechanical damage may come from improper operation during construction or accidental collision during use; microcracks may gradually expand due to uneven stress distribution inside the material or long-term external force; environmental erosion mainly comes from erosion by moisture, acid and alkali and other substances, which will accelerate the aging process of glass fiber board. Once these problems occur, it will not only affect the normal use of glass fiber board, but also may cause safety hazards and threaten people's life and property safety. At present, although some progress has been made in the modification technology of glass fiber board, it mainly focuses on improving its mechanical properties, such as enhancing tensile strength and compressive strength. However, there is relatively little research on damage repair capabilities, which means that fiberglass boards are often difficult to self-recover after being damaged and can only rely on manual replacement or repair, which undoubtedly increases maintenance costs and difficulty.

[0003] As a new type of smart material, self-healing materials can automatically recover from damage under external stimulation, thereby extending the service life of the material. However, existing self-healing material technology still faces many challenges, such as low repair efficiency, limited self-repair times, and decreased mechanical properties after repair. These problems limit the widespread application of self-healing materials in structural materials such as fiberglass boards.

[0004] Therefore, inventing a composite glass fiber board with excellent self-repairing ability not only has important research significance, but also contains huge application value. Summary of the invention

[0005] In view of the above-mentioned existing technical problems, a composite glass fiber board and a preparation method thereof are provided. The composite glass fiber board prepared by this method has excellent mechanical properties and high-efficiency repeated self-repairing ability, and the preparation process is simple and easy to implement.

[0006] The present invention discloses a composite glass fiber board, which is composed of the following components in parts by weight:

[0007] 45-65 parts of polyurethane; 12-16 parts of curing agent; 18-25 parts of glass fiber; 5-6 parts of m-phenylenediamine; 4.8-6 parts of benzaldehyde; 1-2 parts of toughening agent; 0.5-1.5 parts of light stabilizer; 0.05-0.2 parts of heat stabilizer; 1-3 parts of crosslinking regulator.

[0008] Preferably, the light stabilizer is benzotriazole; the heat stabilizer is aluminum hydroxide; the cross-linking regulator is phthalate; and the toughening agent is polyethylene glycol.

[0009] The present invention also discloses a method for preparing a composite glass fiber board, comprising the following preparation steps:

[0010] S1 Preparation of composite glass fiber board matrix: Add polyurethane to the reactor, heat and melt it, add curing agent and toughening agent in sequence while stirring, maintain the original temperature and continue stirring for 30 to 50 minutes after all additions are completed, then immerse glass fiber in the mixed solution, vibrate the reactor to make the glass fiber evenly distributed in the mixed solution, and cool it down to obtain the composite glass fiber board matrix;

[0011] S2 Dynamic Network Liquid Preparation: Place the reaction bottle in an electromagnetic heating jacket, add m-phenylenediamine to the reaction bottle, turn on the electromagnetic stirring of the electromagnetic heating jacket, and then slowly add benzaldehyde to the reaction bottle containing m-phenylenediamine. After all the benzaldehyde has been added, heat the reaction mixture, and after the reaction is completed, a dynamic network liquid is formed;

[0012] S3 composite molding and curing: the composite glass fiber board matrix prepared in step S1 is placed in a tray, the dynamic network liquid prepared in step S2 is poured into the above tray, the tray is placed on an ultrasonic oscillator for oscillation, and then the tray is removed and allowed to stand to allow the dynamic network to be evenly distributed in the matrix, and then the matrix impregnated with the dynamic network liquid is placed in a mold, hot-pressed and cured to obtain a composite glass fiber board.

[0013] Preferably, in step S1 of preparing the composite glass fiber board matrix, the heating and melting temperature in the reactor is 200-360°C.

[0014] Preferably, in step S1 of preparing the composite glass fiber board matrix, the vibration frequency of the reactor is 500-800 Hz; and the vibration duration of the reactor is 1-2 hours.

[0015] Preferably, in the step S1 of preparing the composite glass fiber board matrix, the cooling temperature is 50-70°C.

[0016] Preferably, in the S2 dynamic network liquid preparation step, the temperature of the heating reaction of the electromagnetic heating sleeve is 60 to 80° C.; and the heating reaction time is 2 to 3 hours.

[0017] Preferably, in the S2 dynamic network liquid preparation step, the electromagnetic stirring speed of the electromagnetic heating jacket is 900-1100 rpm.

[0018] Preferably, in the S3 composite molding and curing step, the ultrasonic frequency of the ultrasonic oscillator is 20 to 60 kHz; the ultrasonic oscillation time is 10 to 20 minutes; and the standing time after removing the tray is 20 to 40 minutes.

[0019] Preferably, in the S3 composite molding and curing step, the hot pressing temperature of the hot pressing curing molding is 130-180° C.; the hot pressing pressure of the hot pressing curing molding is 15-30 MPa; and the time of the hot pressing curing molding is 1-3 hours.

[0020] Compared with the prior art, the present invention has the following beneficial effects:

[0021] The present invention provides a composite glass fiber board and a preparation method thereof, which significantly improves the mechanical properties, self-repairing ability and durability of the glass fiber board by constructing a double network structure cross-linked by dynamic imine bonds. The glass fiber board can be quickly repaired by environmental stimulation (such as heat, light, humidity) after being damaged, and the repair process can be repeated many times without complicated operations.

[0022] The polyurethane and glass fiber in the raw materials serve as the main chain structure, providing the basic mechanical properties of the material, forming a rigid and tightly cross-linked network, which is the composite glass fiber board matrix, with this matrix as the first network; metaphenylenediamine and benzaldehyde are used to form a dynamic imine bond network through condensation reaction. This dynamic imine bond network is a soft, tough loosely cross-linked network, with this dynamic network as the second network, and the first network and the second network are combined together by ultrasonic hot pressing curing to finally form a composite glass fiber board with a double network reinforced structure. When the composite glass fiber board is damaged by external force, the first network provides stable mechanical support to ensure that the structural integrity is not lost during the material repair process; the imine bonds of the second network play a dynamic role under stimulation to restore the broken parts, thereby achieving double network synergistic repair.

[0023] The present invention provides a composite glass fiber board having excellent mechanical properties and high-efficiency repeated self-repairing ability, and the preparation process is simple and easy to implement. DETAILED DESCRIPTION

[0024] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.

[0025] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.

[0026] Embodiment 1: A composite glass fiber board, comprising the following components in parts by weight:

[0027] 45 parts of polyurethane; 12 parts of curing agent; 18 parts of glass fiber; 5 parts of m-phenylenediamine; 6 parts of benzaldehyde; 1 part of polyethylene glycol; 0.5 parts of benzotriazole; 0.05 parts of aluminum hydroxide; 1 part of phthalate.

[0028] A method for preparing a composite glass fiber board comprises the following preparation steps:

[0029] Preparation of S1 composite glass fiber board matrix: Add polyurethane to the reactor, heat the reactor temperature to 230℃, heat and melt the polyurethane, add curing agent and polyethylene glycol in sequence while stirring, maintain the original temperature and continue stirring for 40 minutes after all the additions are completed, then immerse the glass fiber in the mixed solution, vibrate the reactor, the vibration frequency of the reactor is 650Hz, and the vibration time is 1.5h, so that the glass fiber is evenly distributed in the mixed solution, cool to 60℃ and cool to obtain the composite glass fiber board matrix.

[0030] Preparation of S2 dynamic network liquid: Place the reaction bottle in an electromagnetic heating jacket, add m-phenylenediamine to the reaction bottle, turn on the electromagnetic stirring of the electromagnetic heating jacket, set the stirring rate to 1000 rpm, and then slowly add benzaldehyde to the reaction bottle containing m-phenylenediamine. After all the benzaldehyde is added, set the temperature of the electromagnetic heating jacket to 70°C to heat the reaction mixture. The heating reaction time is 2.5 hours. After the reaction is completed, a dynamic network liquid is formed;

[0031] S3 composite molding and curing: place the composite glass fiber board matrix prepared in step S1 in a tray, pour the dynamic network liquid prepared in step S2 into the above tray, place the tray on an ultrasonic oscillator, set the vibration frequency of the ultrasonic oscillator to 35kHz for oscillation, remove the tray after oscillating for 15 minutes and let it stand for 30 minutes to allow the dynamic network to be evenly distributed in the matrix, then place the matrix impregnated with the dynamic network liquid in a mold and perform hot pressing curing molding, wherein the hot pressing temperature is 150°C; the hot pressing pressure of the hot pressing curing molding is 25MPa; the hot pressing curing molding time is 2h, and the composite glass fiber board is obtained after the hot pressing curing is completed.

[0032] Embodiment 2: A composite glass fiber board, comprising the following components in parts by weight:

[0033] 50 parts of polyurethane; 14 parts of curing agent; 20 parts of glass fiber; 5.5 parts of m-phenylenediamine; 5.5 parts of benzaldehyde; 1.2 parts of polyethylene glycol; 0.7 parts of benzotriazole; 0.1 parts of aluminum hydroxide; 2 parts of phthalate.

[0034] The preparation method of the composite glass fiber board is the same as the preparation method of Example 1, and the parameter solutions in the method are the same.

[0035] Embodiment 3: A composite glass fiber board, comprising the following components in parts by weight:

[0036] 65 parts of polyurethane; 16 parts of curing agent; 25 parts of glass fiber; 6 parts of m-phenylenediamine; 4.8 parts of benzaldehyde; 2 parts of polyethylene glycol; 1.5 parts of benzotriazole; 0.2 parts of aluminum hydroxide; 3 parts of phthalate.

[0037] The preparation method of the composite glass fiber board is the same as the preparation method of Example 1, and the parameter solutions in the method are the same.

[0038] Embodiment 4: A composite glass fiber board, comprising the following components in parts by weight:

[0039] 60 parts of polyurethane; 15 parts of curing agent; 19 parts of glass fiber; 5.8 parts of m-phenylenediamine; 5.22 parts of benzaldehyde; 1.5 parts of polyethylene glycol; 1.2 parts of benzotriazole; 0.12 parts of aluminum hydroxide; and 1.5 parts of phthalate.

[0040] The preparation method of the composite glass fiber board is the same as the preparation method of Example 1, and the parameter solutions in the method are the same.

[0041] Embodiment 5: A composite glass fiber board, comprising the following components in parts by weight:

[0042] 55 parts of polyurethane; 13 parts of curing agent; 22 parts of glass fiber; 5.2 parts of m-phenylenediamine; 5.72 parts of benzaldehyde; 1.7 parts of polyethylene glycol; 0.9 parts of benzotriazole; 0.15 parts of aluminum hydroxide; and 2.5 parts of phthalate.

[0043] The preparation method of the composite glass fiber board is the same as the preparation method of Example 1, and the parameter solutions in the method are the same.

[0044] Embodiment 6: A composite glass fiber board, comprising the following components in parts by weight:

[0045] 60 parts of polyurethane; 15 parts of curing agent; 19 parts of glass fiber; 5.8 parts of m-phenylenediamine; 5.22 parts of benzaldehyde; 1.5 parts of polyethylene glycol; 1.2 parts of benzotriazole; 0.12 parts of aluminum hydroxide; and 1.5 parts of phthalate.

[0046] A method for preparing a composite glass fiber board comprises the following preparation steps:

[0047] Preparation of S1 composite glass fiber board matrix: Add polyurethane to the reactor, heat the reactor temperature to 200℃, heat and melt the polyurethane, add curing agent and polyethylene glycol in sequence while stirring, and maintain the original temperature and continue stirring for 30 minutes after all the additions are completed. Then immerse the glass fiber in the mixed solution, vibrate the reactor, the vibration frequency of the reactor is 500Hz, and the vibration time is 1h, so that the glass fiber is evenly distributed in the mixed solution, cool to 50℃ and cool to obtain the composite glass fiber board matrix.

[0048] Preparation of S2 dynamic network liquid: Place the reaction bottle in an electromagnetic heating jacket, add m-phenylenediamine to the reaction bottle, turn on the electromagnetic stirring of the electromagnetic heating jacket, set the stirring rate to 900 rpm, and then slowly add benzaldehyde to the reaction bottle containing m-phenylenediamine. After all the benzaldehyde is added, set the temperature of the electromagnetic heating jacket to 60°C to heat the reaction mixture. The heating reaction time is 2 hours. After the reaction is completed, a dynamic network liquid is formed;

[0049] S3 composite molding and curing: place the composite glass fiber board matrix prepared in step S1 in a tray, pour the dynamic network liquid prepared in step S2 into the above tray, place the tray on an ultrasonic oscillator, set the vibration frequency of the ultrasonic oscillator to 20kHz for oscillation, remove the tray after 10 minutes of oscillation and let it stand for 20 minutes to allow the dynamic network to be evenly distributed in the matrix, then place the matrix impregnated with the dynamic network liquid in a mold and perform hot pressing curing molding, wherein the hot pressing temperature is 130°C; the hot pressing pressure of the hot pressing curing molding is 15MPa; the hot pressing curing molding time is 1h, and the composite glass fiber board is obtained after the hot pressing curing is completed.

[0050] Embodiment 7: A composite glass fiber board, comprising the following components in parts by weight:

[0051] 60 parts of polyurethane; 15 parts of curing agent; 19 parts of glass fiber; 5.8 parts of m-phenylenediamine; 5.22 parts of benzaldehyde; 1.5 parts of polyethylene glycol; 1.2 parts of benzotriazole; 0.12 parts of aluminum hydroxide; and 1.5 parts of phthalate.

[0052] A method for preparing a composite glass fiber board comprises the following preparation steps:

[0053] Preparation of S1 composite glass fiber board matrix: Add polyurethane to the reactor, heat the reactor temperature to 260℃, heat and melt the polyurethane, add curing agent and polyethylene glycol in sequence while stirring, and maintain the original temperature and continue stirring for 35 minutes after all the additions are completed. Then immerse the glass fiber in the mixed solution, vibrate the reactor with a vibration frequency of 550Hz and a vibration time of 1.2h to evenly distribute the glass fiber in the mixed solution, cool it to 55℃ and then cool it to obtain the composite glass fiber board matrix.

[0054] Preparation of S2 dynamic network liquid: Place the reaction bottle in an electromagnetic heating jacket, add m-phenylenediamine to the reaction bottle, turn on the electromagnetic stirring of the electromagnetic heating jacket, set the stirring rate to 950 rpm, and then slowly add benzaldehyde to the reaction bottle containing m-phenylenediamine. After all the benzaldehyde is added, set the temperature of the electromagnetic heating jacket to 65°C to heat the reaction mixture. The heating reaction time is 2.2 hours. After the reaction is completed, a dynamic network liquid is formed;

[0055] S3 composite molding and curing: place the composite glass fiber board matrix prepared in step S1 in a tray, pour the dynamic network liquid prepared in step S2 into the above tray, place the tray on an ultrasonic oscillator, set the vibration frequency of the ultrasonic oscillator to 25kHz for oscillation, remove the tray after oscillating for 13 minutes and let it stand for 25 minutes to allow the dynamic network to be evenly distributed in the matrix, then place the matrix impregnated with the dynamic network liquid in a mold and perform hot pressing curing molding, wherein the hot pressing temperature is 140°C; the hot pressing pressure of the hot pressing curing molding is 20MPa; the hot pressing curing molding time is 1.2h, and the composite glass fiber board is obtained after the hot pressing curing is completed.

[0056] Embodiment 8: A composite glass fiber board, comprising the following components in parts by weight:

[0057] 60 parts of polyurethane; 15 parts of curing agent; 19 parts of glass fiber; 5.8 parts of m-phenylenediamine; 5.22 parts of benzaldehyde; 1.5 parts of polyethylene glycol; 1.2 parts of benzotriazole; 0.12 parts of aluminum hydroxide; and 1.5 parts of phthalate.

[0058] A method for preparing a composite glass fiber board comprises the following preparation steps:

[0059] Preparation of S1 composite glass fiber board matrix: Add polyurethane to the reactor, heat the reactor temperature to 300℃, heat and melt the polyurethane, add curing agent and polyethylene glycol in sequence while stirring, and maintain the original temperature and continue stirring for 45 minutes after all the additions are completed. Then immerse the glass fiber in the mixed solution, vibrate the reactor, the vibration frequency of the reactor is 700Hz, and the vibration time is 1.7h, so that the glass fiber is evenly distributed in the mixed solution, cool to 65℃ and cool to obtain the composite glass fiber board matrix.

[0060] Preparation of S2 dynamic network liquid: Place the reaction bottle in an electromagnetic heating jacket, add m-phenylenediamine to the reaction bottle, turn on the electromagnetic stirring of the electromagnetic heating jacket, set the stirring rate to 1050rpm, and then slowly add benzaldehyde to the reaction bottle containing m-phenylenediamine. After all the benzaldehyde is added, set the temperature of the electromagnetic heating jacket to 75°C to heat the reaction mixture. The heating reaction time is 2.7h. After the reaction is completed, a dynamic network liquid is formed;

[0061] S3 composite molding and curing: place the composite glass fiber board matrix prepared in step S1 in a tray, pour the dynamic network liquid prepared in step S2 into the above tray, place the tray on an ultrasonic oscillator, set the vibration frequency of the ultrasonic oscillator to 45kHz for oscillation, remove the tray after oscillating for 13 minutes and let it stand for 35 minutes to allow the dynamic network to be evenly distributed in the matrix, then place the matrix impregnated with the dynamic network liquid in a mold and perform hot pressing curing molding, wherein the hot pressing temperature is 165°C; the hot pressing pressure of hot pressing curing molding is 27MPa; the hot pressing curing molding time is 1.7h, and the composite glass fiber board is obtained after the hot pressing curing is completed.

[0062] Embodiment 9: A composite glass fiber board, comprising the following components in parts by weight:

[0063] 60 parts of polyurethane; 15 parts of curing agent; 19 parts of glass fiber; 5.8 parts of m-phenylenediamine; 5.22 parts of benzaldehyde; 1.5 parts of polyethylene glycol; 1.2 parts of benzotriazole; 0.12 parts of aluminum hydroxide; and 1.5 parts of phthalate.

[0064] A method for preparing a composite glass fiber board comprises the following preparation steps:

[0065] Preparation of S1 composite glass fiber board matrix: Add polyurethane to the reactor, heat the reactor temperature to 360℃, heat and melt the polyurethane, add curing agent and polyethylene glycol in sequence while stirring, and maintain the original temperature and continue stirring for 50 minutes after all the additions are completed, then immerse the glass fiber in the mixed solution, vibrate the reactor, the vibration frequency of the reactor is 800Hz, and the vibration time is 2h, so that the glass fiber is evenly distributed in the mixed solution, cool to 70℃ and cool to obtain the composite glass fiber board matrix.

[0066] Preparation of S2 dynamic network liquid: Place the reaction bottle in an electromagnetic heating jacket, add m-phenylenediamine to the reaction bottle, turn on the electromagnetic stirring of the electromagnetic heating jacket, set the stirring rate to 1100 rpm, and then slowly add benzaldehyde to the reaction bottle containing m-phenylenediamine. After all the benzaldehyde is added, set the temperature of the electromagnetic heating jacket to 75°C to heat the reaction mixture. The heating reaction time is 3 hours. After the reaction is completed, a dynamic network liquid is formed;

[0067] S3 composite molding and curing: place the composite glass fiber board matrix prepared in step S1 in a tray, pour the dynamic network liquid prepared in step S2 into the above tray, place the tray on an ultrasonic oscillator, set the vibration frequency of the ultrasonic oscillator to 60kHz for oscillation, remove the tray after oscillating for 20 minutes and let it stand for 40 minutes to allow the dynamic network to be evenly distributed in the matrix, then place the matrix impregnated with the dynamic network liquid in a mold and perform hot pressing curing molding, wherein the hot pressing temperature is 180°C; the hot pressing pressure of the hot pressing curing molding is 30MPa; the hot pressing curing molding time is 2h, and the composite glass fiber board is obtained after the hot pressing curing is completed.

[0068] The performance of the composite glass fiber boards prepared in Examples 1 to 9 was tested, and the test results are shown in the following table:

[0069] Table 1

[0070]

[0071]

[0072] It can be seen from the test data in the above table that the tensile strength of the composite glass fiber boards prepared in Examples 1 to 9 is not less than 800MPa, the compressive strength is not less than 100MPa, the heat resistance temperature is not less than 500°C, and the density is not less than 1.6. Therefore, the composite glass fiber boards prepared in Examples 1 to 9 have good mechanical properties and heat resistance, and their own density is moderate. Among them, Examples 1 to 5 are for screening the proportions of various raw materials of the composite glass fiber boards. It can be seen from the test data that the composite glass fiber board prepared in Example 4 has the best performance. Therefore, the raw material ratios in Example 4 are the best; Examples 1 and Examples 6 to 9 are for screening the combination of various parameters in the preparation method. It can also be seen from the test data that the composite glass fiber board prepared in Example 8 has the best performance.

[0073] The self-repairing performance of the composite glass fiber boards prepared in Examples 1 to 9 was tested. Specifically, a scratch of 100 μm deep was scratched on the surface of the glass fiber board, and the scratch repair effect was observed after being placed in a 60° C. environment for 1 hour. The test results are shown in the following table:

[0074] Table 2

[0075] Example Scratch depth reduction (%) Repair efficiency (%) Mechanical strength recovery rate (%) 1 90.0 95.0 93.0 2 92.0 95.3 94.1 3 93.5 95.6 95.2 4 95.1 96.2 96.5 5 95.0 96.0 96.4 6 90.5 95.1 93.6 7 94.3 95.8 95.5 8 96.6 97.0 97.0 9 91.8 95.5 96.0

[0076] As shown in the self-repair test data in the above table, the composite glass fiber boards prepared in Examples 1 to 9 all have certain self-repair capabilities, among which Example 8 has the best self-repair capability and the fastest repair rate.

[0077] In summary, from the data in Table 1 and Table 2, it can be seen that the composite glass fiber board prepared in Example 8 has the best comprehensive performance, from which we can obtain that the weight ratio of each raw material in the composite glass fiber board provided by the present invention is 60 parts of polyurethane; 15 parts of curing agent; 19 parts of glass fiber; 5.8 parts of m-phenylenediamine; 5.22 parts of benzaldehyde; 1.5 parts of polyethylene glycol; 1.2 parts of benzotriazole; 0.12 parts of aluminum hydroxide; 1.5 parts of phthalate. The parameters of the best preparation method are shown in Example 8.

[0078] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the scope of protection of the invention.

Claims

1. A composite glass fiber board, characterized in that: It is composed of the following ingredients in parts by weight: 45-65 parts of polyurethane; 12-16 parts of curing agent; 18-25 parts of glass fiber; 5-6 parts of m-phenylenediamine; 4.8-6 parts of benzaldehyde; 1-2 parts of toughening agent; 0.5-1.5 parts of light stabilizer; 0.05-0.2 parts of heat stabilizer; 1-3 parts of crosslinking regulator.

2. A composite glass fiber board according to claim 1, characterized in that: The light stabilizer is benzotriazole; the heat stabilizer is aluminum hydroxide; the cross-linking regulator is phthalate; and the toughening agent is polyethylene glycol.

3. A method for preparing a composite glass fiber board, characterized in that: The method comprises the following preparation steps: S1 Preparation of composite glass fiber board matrix: Add polyurethane to the reactor, heat and melt it, add curing agent and toughening agent in sequence while stirring, maintain the original temperature and continue stirring for 30 to 50 minutes after all additions are completed, then immerse glass fiber in the mixed solution, vibrate the reactor to make the glass fiber evenly distributed in the mixed solution, and cool it down to obtain the composite glass fiber board matrix; S2 Dynamic Network Liquid Preparation: Place the reaction bottle in an electromagnetic heating jacket, add m-phenylenediamine to the reaction bottle, turn on the electromagnetic stirring of the electromagnetic heating jacket, and then slowly add benzaldehyde to the reaction bottle containing m-phenylenediamine. After all the benzaldehyde has been added, heat the reaction mixture, and after the reaction is completed, a dynamic network liquid is formed; S3 composite molding and curing: the composite glass fiber board matrix prepared in step S1 is placed in a tray, the dynamic network liquid prepared in step S2 is poured into the above tray, the tray is placed on an ultrasonic oscillator for oscillation, and then the tray is removed and allowed to stand to allow the dynamic network to be evenly distributed in the matrix, and then the matrix impregnated with the dynamic network liquid is placed in a mold, hot-pressed and cured to obtain a composite glass fiber board.

4. The method for preparing a composite glass fiber board according to claim 3, characterized in that: In the step S1 of preparing the composite glass fiber board matrix, the heating and melting temperature in the reactor is 200-360°C.

5. The method for preparing a composite glass fiber board according to claim 3, characterized in that: In the step S1 of preparing the composite glass fiber board matrix, the vibration frequency of the reactor is 500 to 800 Hz; and the vibration time of the reactor is 1 to 2 hours.

6. The method for preparing a composite glass fiber board according to claim 3, characterized in that: In the step S1 of preparing the composite glass fiber board matrix, the cooling temperature is 50-70°C.

7. The method for preparing a composite glass fiber board according to claim 3, characterized in that: In the S2 dynamic network liquid preparation step, the temperature of the electromagnetic heating sleeve heating reaction is 60-80° C.; the heating reaction time is 2-3 hours.

8. The method for preparing a composite glass fiber board according to claim 3, characterized in that: In the S2 dynamic network liquid preparation step, the electromagnetic stirring speed of the electromagnetic heating jacket is 900-1100 rpm.

9. The method for preparing a composite glass fiber board according to claim 3, characterized in that: In the S3 composite molding and curing step, the ultrasonic frequency of the ultrasonic oscillator is 20 to 60 kHz; the ultrasonic oscillation time is 10 to 20 minutes; and the standing time after removing the tray is 20 to 40 minutes.

10. The method for preparing a composite glass fiber board according to claim 3, characterized in that: In the S3 composite molding and curing step, the hot pressing temperature of the hot pressing curing molding is 130-180° C.; the hot pressing pressure of the hot pressing curing molding is 15-30 MPa; and the time of the hot pressing curing molding is 1-3 hours.

Citation Information

Cited By

  • High-strength glass fiber board and application thereof in automobiles

    CN120648164A